Cyber Resistance: An educational game prototype for teaching cybersecurity - Souza, Maria Vitória Polido de; Sangaleti, Juliano Rubio; Campiolo, Rodrigo; Almeida, Marcos Silvano; Santos, Luiz Arthur Feitosa dos (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on CybersecurityDO - 10.5753/sbseg_estendido.2025.11869, 2025)
This article presents ongoing work on the development and evaluation of an educational game aimed at promoting cybersecurity learning. The scenarios and characters are being developed using the Godot engine, following an incremental and modular process to enable the integration of various gamified activities. As partial results, the initial scenario and characters have been created, along with gamified quiz and logic challenge activities. The game has shown promising outcomes in a preliminary evaluation conducted with Computer Science students.